Examining the expectations of local people about sports services in local governments on different variables - Ekin Abdulkadir; Kizilkaya Kemal; Buyrukoğlu Erhan; Şahan Hasan (SHS Web of Conferences)
According to Articles 58 and 59 of the 1982 Constitution, “The State protects young people, keeps them away from bad habits and encourages them to sports” and “Local governments are responsible for meeting the needs of local people". In line with these articles, in our research, it was aimed to examine the expectations of local people about sports services in local governments on different variables. 460 (Female; N= 268, 58.3%, Male; N=192, 41.7%) individuals who voluntarily agreed to participate in our research residing in Siirt province in 2024 constitute the sample group of our research. ’’Scale of People’s Expectations from Municipalities on Sports Services’’ developed by Çoban [5] was used. The research data were analyzed in SPSS, 25 package program. As a result of the normality analysis of the scale, it was seen that the significance values were greater than 0.05 and it was decided to use nonparametric analyses (Man Witney U, Kruskal Wallis H) in the analysis. According to the results of the analyses, no statistically significant difference was found in the variables of gender, educational status, and monthly income (p>0.05), while a statistical difference was found in the variables of marital status and occupation (p<0.05).